2017
DOI: 10.3892/ol.2017.6346
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol-induced apoptosis in human nasopharyngeal carcinoma is associated with the activation of the death receptor and the mitochondrial pathway

Abstract: Abstract. Nasopharyngeal carcinoma (NPC) is a cancer that arises from the epithelium of the nasopharynx. Celastrol is a triterpene from traditional Chinese medicine, which demonstrates anti-proliferative activity in several cancer cell lines. However, the effect of celastrol on human NPC and the underlying mechanisms are not yet elucidated. The present study investigated whether celastrol induced apoptosis in human NPC cells, and the underlying molecular mechanisms were explored. Celastrol decreased the viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Expression of cleaved PARP (p85) was also increased compared with control cells, altogether indicating that induction of the caspase apoptotic pathway may be one mechanism for brevilin-A-induced cell apoptosis. This is consistent with previous articles, which showed that cleaved caspase 9 and cleaved PARP were found in apoptotic cells after treatment with brevilin A (Lin et al, 2017; Wang et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Expression of cleaved PARP (p85) was also increased compared with control cells, altogether indicating that induction of the caspase apoptotic pathway may be one mechanism for brevilin-A-induced cell apoptosis. This is consistent with previous articles, which showed that cleaved caspase 9 and cleaved PARP were found in apoptotic cells after treatment with brevilin A (Lin et al, 2017; Wang et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Expression of cleaved PARP (p85) was also increased, altogether suggesting the caspase apoptotic pathway as a mechanism for arnicolide-D-induced cell apoptosis. This is consistent with previous studies that showed increased cleaved caspase 9 and cleaved PARP in apoptotic cells [27,39].…”
Section: Discussionsupporting
confidence: 94%
“…TCM has been developed for cancer research and many Chinese herbal medicines have been demonstrated to inhibit cancer. Celastrol is a triterpene from TCM, which demonstrates anti-proliferative activity in HONE-1 and NPC-039 cell lines and induces apoptosis through the death receptor and mitochondrial pathway in human NPC cells, which makes it a promising candidate in the development of drugs for treating NPC ( 24 ). Evodiamine inhibits the migration and invasive ability of NPC cells and metastasis targeting matrix metalloproteinase-2 ( 25 ).…”
Section: Discussionmentioning
confidence: 99%